2001
DOI: 10.1136/adc.85.5.398
|View full text |Cite
|
Sign up to set email alerts
|

Genes and environment in asthma: a study of 4 year old twins

Abstract: Results-Univariate parameter estimates derived from model fitting were 68% heritability, 13% shared environment, and 19% non-shared environment. Conclusions-Our findings suggest that asthma is highly heritable in 4 year olds, whereas shared environmental influences are not statistically significant. (Arch Dis Child 2001;85:398-400)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 26 publications
4
31
0
2
Order By: Relevance
“…In this context genetic predisposition towards being atopic and asthmatic would appear to be a crucial feature of wheezing persistence, confirming results such as those of KOEPPEN-SCHOMERUS et al [11] who, in a recent study of twin pairs, showed that heritable factors predominate over shared environmental influences in asthma development. The present findings add to those of CSONKA et al [12] who retrospectively looked at risk factors for wheezing persistence in their study group, and confirm the importance of heredity towards the persistent asthmatic phenotype suggested by LONDON et al [13].…”
Section: Discussionsupporting
confidence: 77%
“…In this context genetic predisposition towards being atopic and asthmatic would appear to be a crucial feature of wheezing persistence, confirming results such as those of KOEPPEN-SCHOMERUS et al [11] who, in a recent study of twin pairs, showed that heritable factors predominate over shared environmental influences in asthma development. The present findings add to those of CSONKA et al [12] who retrospectively looked at risk factors for wheezing persistence in their study group, and confirm the importance of heredity towards the persistent asthmatic phenotype suggested by LONDON et al [13].…”
Section: Discussionsupporting
confidence: 77%
“…The general result from twin studies is that asthma is a highly heritable trait. Approximately 70% of the variance in liability to asthma is explained by genetic factors [5][6][7][8][9][10][11]. If there were sex differences in genetic factors, then the influence of genetic factors was usually lower for females than males.…”
mentioning
confidence: 99%
“…The precise cause of asthma is still unknown, but the disorder is most likely a combination of environmental factors, such as air pollution and tobacco smoke exposure, and genetic factors (London, 2007;Ober & Hoffjan, 2006;Vercelli, 2004). Twin studies have shown heritability estimates for asthma to be high, ranging from 60% to 90% (e.g., Duffy et al, 1990;Harris et al, 1997;Koeppen-Schomerus et al, 2001;Laitinen et al, 1998;Skadhauge et al, 1999;van Beijsterveldt & Boomsma, 2007). Significant gene-environment interactions are likely to be present, probably representing the genetic regulation of immune responses to environmental factors and allergens and the tissue-repair processes which ultimately lead to asthma (Ober & Thompson, 2005;Yang et al, 2007).…”
mentioning
confidence: 99%